Cultural Values in the Novel “Charlotte’s Web - E.B White”: Literary anthropology Approach - Kheryadi Kheryadi; Zuriyati Zuriyati; Ninuk Lustyantie (English Education Department, 2021)
Abstract: The purpose of this research is to learn more about the cultural value of the novel Charlotte’s Web - E.B White. The qualitative descriptive technique was used in this study, which is based on the literary anthropology approach. The information was gathered by carefully reading the text, identifying, and categorizing it. The goal of this study is to help find the friendship depicted in the novel Charlotte's Web. This study focuses on the many forms of friendship and how they are depicted in the novel. W. D. Ross (1999) theory was used to identify and classify the data, while Robert Stanton's (1965) theory was utilized to analyze the friendship depicted in the novel Charlotte's Web. The findings of this study reveal three forms of friendship in the characters represented. The three forms of friendship are as follows: 1) friendship of utility, 2) friendship of pleasure, and 3) friendship of kindness.